Mobile Opportunistic Commerce: Mechanisms, Architecture, and Application - Kamar, Ece; Horvitz, Eric; Meek, Chris (In Proceedings of AAMAS 2008, 2008)
We present mechanisms, architectures, and an implementation addressing challenges with mobile opportunistic commerce centering on markets and mechanisms that support the procurement of goods and services in mobile settings. Our efforts seek to extend core concepts from research in electronic commerce to interactions between mobile buyers and brick and mortar businesses that have geographically situated retail offices. We focus on efficient mechanisms, infrastructure, and automation that can enable sellers and buyers to take joint advantage of the relationship of the locations of retail offices to the routes of mobile buyers who may have another primary destination. The methods promote automated vigilance about opportunities to buy and sell, and to support negotiations on the joint value to buyers and sellers including buyers’ costs of divergence from their original paths to acquire services and commodities. We extend prior work on auction mechanisms to personal procurement settings by analyzing the dynamics of the cost to buyers based on preexisting plans, location, and overall context. We present mechanisms for auctions in single item, combinatorial, and multiattribute settings that take into consideration personal inconvenience costs within time sensitive dynamic markets and challenges with privacy and fairness.